(untitled) (Prithvi Academic Journal, 2023)
Studies in the global context show a variation in the occupational relationships in between father-son, father-daughter, mother-son and mother-daughter. However, such studies in Nepal are insufficient. This paper describes the socio-demographic features of people in between successive generations, and their occupational relationships, typically of father and son. A semi-structured questionnaire schedule was used to collect information from a total of 385 father son pairs during June to September 2018 in Gajuri Rural Municipality of Bagmati Province, Dhading District, Nepal. Information was collected from those fathers whose eldest son got married by the time of interview. The findings from bivariate analysis revealed that along with the changes of several socio-economic variables in the rural households in Nepal, there is both continuity and change in the parental occupations in between the father and son. Among various characteristics of father, the level of education and monthly income, in the case of son’s characteristics, the level of education and migration; and in the case of household characteristics, the caste/ethnicities and residential locations were related with the father-son occupational change. Hence, these findings indicate that the rural society in Nepal is undergoing socio-economic transformations; there is both continuity and change of fathers’ occupation by the son.